Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am looking to evaluate

$$\int_0^1 x \sinh (x) \ \mathrm{dx}$$

share|cite|improve this question
integration by parts – Will Jagy Sep 21 '12 at 2:34

Use integration by parts! General format:

$$\int f(x) g'(x)dx = f(x)g(x)-\int f'(x)g(x)dx$$

Remember! If you have bounds on the integral, they must be applied to the $f(x)g(x)$ part, too (this proceeds in the normal way).

So, if I recall correctly, the integral of $\sinh(x)$ is $\cosh(x)$...

So following the integration by parts formula, we see that

$\int_0^1 x\sinh(x)dx = (x\cosh(x)|_0^1 - \int_0^1 \cosh(x)dx$

$=\cosh(1)-[\sinh(1)-\sinh(0)] = \cosh(1) -\sinh(1) + \sinh(0)$

$=\cosh(1) - \sinh(1)$

I'm sure there's some tricky identity after that, but that's as far as I go.

share|cite|improve this answer
well not quite a tricky identity, but $\cosh 1-\sinh 1=1/e$ immediately from their definitions – Jonathan Sep 21 '12 at 4:48

You can also make use of the fact, that you can rewrite the integral:

$$\int_0^1 xf(x)\,\mathrm dx = \int_0^1 f(x) \int_0^x 1 \,\mathrm dy\,\mathrm dx.$$

This is just the integral over the right-angled triangle and using Fubini's theorem you arrive at $$\int_0^1 1 \int_y^1 f(x) \,\mathrm dx \,\mathrm dy.$$

Inserting $f(x) = \sinh(x)$ you get $$\int_0^1 x\sinh(x)\,\mathrm dx = \int_0^1 \int_y^1 \sinh(x)\,\mathrm dx\,\mathrm dy = \int_0^1 \cosh(1) - \cosh(y)\,\mathrm dy = \cosh(1) - \sinh(1).$$

share|cite|improve this answer

$2\sinh(x)=e^x-e^{-x}$ and $\int e^x(f(x)+f'(x))dx=e^xf(x)$

Thus, $$2\int_0^1 x \sinh (x)dx=\int_0^1 xe^xdx-\int_0^1 xe^{-x}dx$$ $$=\int_0^1 e^x(x+1)dx-\int_0^1 e^{-x}(-x+1)d(-x)-\int_0^1 e^{x}dx+\int_0^1 e^{-x}d(-x)$$ $$=xe^x|_0^1-(-xe^{-x})|_0^1-e^x|_0^1+e^{-x}|_0^1$$ $$=e+\frac{1}{e}-(e-1)+(\frac{1}{e}-1)=\frac{2}{e}$$

Hence, $$2\int_0^1 x \sinh (x)dx=\frac{2}{e}\implies \int_0^1 x \sinh (x)dx=\frac{1}{e}$$

share|cite|improve this answer

If you use Taylor's series representation of the integrand and then interchange the sum and integral, you simply get

$$\sum_{k=0}^{\infty} \left(\frac{1}{(2k+2)!}-\frac{1}{(2k+3)!}\right) = \frac{1}{e}.$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.